Uncertainties in slip-rate estimates for the Mission Creek strand of the southern San Andreas fault at Biskra Palms Oasis, southern California - Behr,WM; Rood,DH; Fletcher,KE; Guzman,N; Finkel,R; Hanks,TC; Hudnut,KW; Kendrick,KJ; Platt,JP; Sharp,WD; Weldon,RJ; Yule,JD (Bulletin of the Geological Society of America, 2010)
This study focuses on uncertainties in estimates of the geologic slip rate along the Mission Creek strand of the southern San Andreas fault where it offsets an alluvial fan (T2) at Biskra Palms Oasis in southern California. We provide new estimates of the amount of fault offset of the T2 fan based on trench excavations and new cosmogenic 10Be age determinations from the tops of 12 boulders on the fan surface. We present three alternative fan offset models: a minimum, a maximum, and a preferred offset of 660 m, 980 m, and 770 m, respectively. We assign an age of between 45 and 54 ka to the T2 fan from the 10Be data, which is significantly older than previously reported but is consistent with both the degree of soil development associated with this surface, and with ages from U-series geochronology on pedogenic carbonate from T2, described in a companion paper by Fletcher et al. (this volume). These new constraints suggest a range of slip rates between ~12 and 22 mm/yr with a preferred estimate of ~14-17 mm/yr for the Mission Creek strand of the southern San Andreas fault. Previous studies suggested that the geologic and geodetic slip-rate estimates at Biskra Palms differed. We find, however, that considerable uncertainty affects both the geologic and geodetic slip-rate estimates, such that if a real discrepancy between these rates exists for the southern San Andreas fault at Biskra Palms, it cannot be demonstrated with available data. © 2010 Geological Society of America.